KARTINI, Majalah Wanita, No.2368/ Tanggal 20 Feb- 06 mar 2014 ( Nurlince sianturi rela berikan satu ginjalnya demi kelangsunan hidup ayahnya ) - Bram Tuapattinaya (PT.Kartini Cahaya Lestari, 2014)
--28 Cm--138 hal.